THE EFFORTS TO FULFILL THE RIGHTS OF JUVENILE INMATES IN ACCESS AND HEALTH FACILITIES IN LPKA CLASS II JAKARTA - Arzethy, Putri Laura; Muhammad, Ali (Universitas Nusa Cendana, 2025)
To evaluate the extent to which the health rights of Juvenile Inmates are fulfilled and the impact of health facilities on their welfare. The background of this study is the importance of fulfilling the health rights of Juvenile Inmates as part of human rights that must be fulfilled, even though they are undergoing a period in the Juvenile Detention Center (LPKA) Class II Jakarta. The method used is a qualitative approach with data collection techniques in the form of in-depth interviews, direct observation, and documentation studies. The results of the study indicated that there was an increase in efforts by the LPKA in providing access to health, but there are still several challenges. It is hoped that this study can be a basis for improving health policies for juvenile inmates in similar institutions. Keywords: Rights of Juvenile Inmates; Health Facilities; Health Programs